Ответ:
Пошаговое объяснение:
1)sin40° + sin16°=2sin(40°+16°)/2)*cos((40°-16°)/2)=2sin28°cos12°
Formuła sina+sinβ=2sin(a+β)/2*cos(a-β)/2
2)sin20°-sin40°=2sin(20°-40°)/2*cos(20°+40°)/2=2sin(-10°)*cos30°= =-2sin10°*cos30°=-2sin10°*√3/2=-√3sin10°
*formuła sina-sinb=2sin(a-β)/2*cos(a+β)/2 , cos 30°=√3/2
3)cos46°-cos74°=-2sin(46°+74°)/2*sin(46°-74°)/2= =-2sin60°*sin(-28°)=2sin60°*sin28°=√3*sin28°
*formuła cosa-cosβ=-2sin(a+β)/2*sin(a-β)/2 ,sin60°=√3/2
4)cos15°+cos45°=2cos(15°+45°)/2*cos(15°-45°)/2=2cos30°*cos(-15°)= -2cos30*cos15=-2*V3/2*cos15 =-V3cos15=-V3*(V6+V2)/4= =-(√18+√6)/4
*formuła cosa+cos=2cos(a+β)/2*cos(a-β)/2 ,cos30°=√3/2 , cos15°=(√6+√2)/4
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
1)sin40° + sin16°=2sin(40°+16°)/2)*cos((40°-16°)/2)=2sin28°cos12°
Formuła sina+sinβ=2sin(a+β)/2*cos(a-β)/2
2)sin20°-sin40°=2sin(20°-40°)/2*cos(20°+40°)/2=2sin(-10°)*cos30°= =-2sin10°*cos30°=-2sin10°*√3/2=-√3sin10°
*formuła sina-sinb=2sin(a-β)/2*cos(a+β)/2 , cos 30°=√3/2
3)cos46°-cos74°=-2sin(46°+74°)/2*sin(46°-74°)/2= =-2sin60°*sin(-28°)=2sin60°*sin28°=√3*sin28°
*formuła cosa-cosβ=-2sin(a+β)/2*sin(a-β)/2 ,sin60°=√3/2
4)cos15°+cos45°=2cos(15°+45°)/2*cos(15°-45°)/2=2cos30°*cos(-15°)= -2cos30*cos15=-2*V3/2*cos15 =-V3cos15=-V3*(V6+V2)/4= =-(√18+√6)/4
*formuła cosa+cos=2cos(a+β)/2*cos(a-β)/2 ,cos30°=√3/2 , cos15°=(√6+√2)/4